(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study examines the impact of Entrepreneurial Orientation on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Semarang City, with innovation ambidexterity and organizational ambidexterity serving as parallel mediators. Using an explanatory quantitative design, data were collected from 52 MSME owners and managers through structured questionnaires and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4.1. The results indicate that EO does not have a direct influence on MSME performance. However, EO significantly affects both innovation ambidexterity and organizational ambidexterity. Among them, only innovation ambidexterity demonstrates a significant effect on performance and successfully mediates the EO–performance relationship, while organizational ambidexterity does not. These findings conclude that innovation ambidexterity is the key mechanism through which EO enhances performance. The study contributes theoretically by clarifying inconsistent prior results and practically by highlighting the importance of balanced innovation strategies to strengthen MSME competitiveness. Keywords: MSMEs Performance, Entrepreneurial Orientation, Innovation Ambidexterity, Organizational Ambidexterity, Parallel Mediation